Analisis Hubungan Korupsi, Demokrasi dan Pertumbuhan Ekonomi di Indonesia - Lucia Maison Putri; Mike Triani (Universitas Negeri Padang, 2021)
The study was conducted to: (1) Determine the response to corruption resulting from the shock of democracy and economic growth in Indonesia. (2) Knowing the democratic response resulting from the shock of corruption and economic growth in Indonesia. (3) Knowing the response to economic growth due to the shock of corruption and democracy in Indonesia. The data used in this study are secondary data, sourced from the KPK annual report website and sourced from BPS (Badan Statistics Center). VAR analysis method is used to determine the two-way relationship between variables. The results of the research are: (1) There is no causal relationship between corruption and democracy. However, there is only a one-way relationship between corruption and democracy (2) There is no causal relationship between corruption and economic growth. However, there is only a one-way relationship between corruption and growth. economy (3) There is no causal relationship between democracy and economic growth. However, there is only a one-way relationship between democracy and economic growth. Based on the research results, it is suggested that the Government can implement policies in handling cases of corruption and democracy because it will affect the welfare of society and the government system in Indonesia. The government also pays more attention to the public sector and the community's economic sector so that they can contribute to improving the welfare of the communityu